Maximizing the output power of magnetically geared generator in low-speed applications using subdomain modeling and particle swarm optimization - Manh-Dung Nguyen; Su-Min Kim; Hyo-Seob Shin; Kyung-Hun Shin; Anh-Tuan Phung; Jang-Young Choi (AIP Advances, 2024)
This study presents an approach to optimizing the output power in a magnetically geared generator by employing subdomain modeling and particle swarm optimization. Accordingly, the subdomain analytical method is utilized to obtain the induced voltage, inductance which are used to predict output power. Afterward, the swarm intelligence optimization technique is applied to reach the maximum output power point. The 12/17/15 prototype evaluated the proposed model by comparing the calculated results and finite element method simulation.